(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2020)
Reseña de libro: Gephart, Werner (ed.). In the Realm of Corona Normativities A Momentary Snapshot of a Dynamic Discourse. Frankfurt: Vittorio Klostermann Verlag, Käte Hamburger Kolleg, 2020.